PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA N-MAX DI KECAMATAN MENGWI BADUNG - Dewa Nyoman Bayu Andhika; Ni Made Hartini (Universitas Triatma Mulya, 2023)
The automotive industry is currently undergoing intense global competition. The Yamaha Company is a business that produces two-wheeled vehicles. The newest scooter motorcycle from Yamaha, the N-MAX, features a number of cutting-edge features, including VVA (Variable Velves Actuation). This study aimed to determine which independent variables had the most significant impact on Mengwi Badung District residents' decisions to purchase Yamaha N-MAX motorcycles by examining the relationship between product quality and price and purchasing decisions. Purposive sampling was used, and the sample size was 85 respondents. Techniques for gathering data that include observational methods, documentation, and surveys. Multiple linear regression analysis is the data analysis technique used. The results of the research's testing of the research hypotheses reveal that the price and product quality variables both have positive and significant effects on the Mengwi Badung District's decision to buy Yamaha N-MAX motorcycles.